2010
DOI: 10.3109/13697130903568534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abrupt discontinuation versus gradual dose reduction of postmenopausal hormone therapy on hot flushes

Abstract: Discontinuation of HT by reducing the daily dose of estrogen for a period of 2 or 4 months did not differ in its effect from that of abrupt cessation with regard to vasomotor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Given that case 1 discontinued HR 3 months prior to PRP treatment, the potential influence of HR requires further consideration. Several RCTs and comparative cohort studies on the effect of HR in menopausal women have shown that menopausal symptoms reoccur after 3 months of discontinuing HR 40 . In light of this data, HR administration for patient 1 may be safely viewed as an independent characteristic unrelated to the effectiveness of PRP treatment 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that case 1 discontinued HR 3 months prior to PRP treatment, the potential influence of HR requires further consideration. Several RCTs and comparative cohort studies on the effect of HR in menopausal women have shown that menopausal symptoms reoccur after 3 months of discontinuing HR 40 . In light of this data, HR administration for patient 1 may be safely viewed as an independent characteristic unrelated to the effectiveness of PRP treatment 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Half of the women in each group resumed HT within a year. 27 Overall, little data are available on tapered approaches to HT discontinuation. Longer and gradual tapers might successfully ease women off HT.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the few randomized clinical trials to date comparing abrupt discontinuation (Bcold turkey[) with tapering provide little evidence to prefer one method to another. 25 Abrupt discontinuation and tapering have been compared in observational studies, but women who elect to taper differ from those who choose abrupt discontinuation, 21,26 complicating a causal interpretation. 8,24 Another study found no differences 9 to 12 months after discontinuation, although the abruptdiscontinuation group had higher rates of VMS at 3 months but lower rates of VMS at 6 months.…”
mentioning
confidence: 99%